Non-genetic factors affecting growth of Kutchi goats - YADAV, J S; YADAV, M C; KHAN, B U (The Indian Journal of Animal Sciences, 2011)
The effect of non-genetic factors on growth traits was studied along with estimation of genetic and phenotypic parameters, in Kutchi goats. The traits included were body weights at birth, 3 months, 6 n10nths, 9 months and 12 months of age. Sex, types of birth, season of birth, fillial generation were used as main effects and dam’s body weight at kidding and birth weight as covariates. The variation in birth weight due to’sex and type ,of birth were significant. Significant’ variation was observed in growth of kids dueto season of birth. Sire, year, season and sex revealed that these traits are positively correlated with growth of kids. Â